Heat-killed Enterococcus faecalis Alters Nitric Oxide and CXCL12 Production but not CXCL8 and CCL3 Production by Cultured Human Dental Pulp Fibroblasts - Sipert, Carla R.; Moraes, Ivaldo G.; Bernardinelli, Norberti; Garcia, Roberto B.; Bramante, Clovis M.; Gasparoto, Thais H.; Figueira, Eduardo A.; Dionisio, Thiago J.; Campanelli, Ana P.; Oliveira, Sandra Helena Penha de [UNESP]; Cunha, Fernando Q.; Santos, Carlos F. (Elsevier B.V., 2010)
Introduction: Fibroblasts are the most abundant cells in dental pulp. To investigate their capacity to produce the chemokines CCL3, CXCL8, and CXCL12 as well as nitric oxide (NO), we evaluated the production of these mediators in supernatants of cultured human dental pulp fibroblasts (HDPF) stimulated by heat-killed Enterococcus faecalis (HKEF). Methods: Primary cultures of HDPF were stimulated with medium alone or HKEF (1:1, 10:1, or 100:1 bacteria:fibroblast) for 1, 6, and 24 hours. Chemokines and NO were assessed through enzyme-linked immunosorbent assay and Griess reaction, respectively. Statistical analysis was performed by using analysis of variance and Tukey post test. Results: CCL3 was not detected, whereas constitutive CXCL8 was not affected. Production of CXCL12 was increased at 1 and 6 hours, and NO was increased at the concentration of 1:1 bacteria:fibroblast at 24 hours. Viability and proliferation assays did not reveal cell number differences. Conclusions: These findings demonstrate that heat-killed E. faecalis is able to increase production of CXCL12 and NO by HDPF. (J Endod 2010;36:91-94)
Keywords: CCL3; chemokines; CXCL8; CXCL12; dental pulp fibroblasts; Enterococcus faecalis; innate immunity; nitric oxide; pulpitis